Examining the role of environmental sustainability measures cleanliness, health, safety, and its impact on visitors satisfaction and perception of service quality at expo 2020, Dubai - Phoebe Andre Fuentes; Noor un Nisa Shahani; Muhammad Nawaz Baloch (Journal of Advanced Research in Social Sciences and Humanities, 2022)
Aim: This research paper examined the role of environmental sustainability measures, including cleanliness, healthy, and safety, and their impact on visitors’ satisfaction and perception of service quality at Expo 20 20 Dubai. To limit the extent of the review, the analyst focused primally on the tourist sector of the United Arab Emirates. This constrained the outcome of the research and established research boundaries. Methodology: The analyst examined 3 to 5 tourists and 3 students or locals from various places to get the result. The qualitative technique was conveyed using an interview format. Findings: The major findings point to positive and encouraging reactions from locals and tourists, as well as opportunities to raise residents’ level of engagement to make the event a success. The key discoveries from Expo 2020 Dubai will assist policymakers and decision-makers in the Dubai economy. Implications/Novel Contribution: The major findings point to positive and encouraging reactions from locals and tourists, as well as opportunities to raise residents’ level of engagement to make the event a success. The key discoveries from Expo 2020 Dubai will assist policymakers and decision-makers in the Dubai economy.